An Overview of Pulmonary Tuberculosis Patients’ Knowledge Regarding Treatment Interruption of Anti-Tuberculosis Drugs (OAT) at Batang Beruh Community Health Center - Sardiaty Sardiaty; Jenri Nababan; Aestetis Parapat (Sean Institute, 2026)
Pulmonary tuberculosis is an infectious disease that affects the lungs and is characteristically marked by the formation of granulomas that lead to tissue necrosis. Pulmonary tuberculosis is caused by Mycobacterium tuberculosis, a rod-shaped bacterium measuring approximately 1–4 µm in length and 0.3–0.6 µm in width. According to the World Health Organization (WHO) in 2007, the number of tuberculosis cases in Indonesia was approximately 528,000, ranking Indonesia third worldwide after India and China. A WHO report in 2009 recorded that Indonesia ranked fifth globally with 429,000 tuberculosis cases, following India, China, South Africa, and Nigeria (WHO Global Tuberculosis Control, 2010). This study aimed to describe the level of knowledge of pulmonary tuberculosis patients regarding the interruption of anti-tuberculosis drug (OAT) treatment at Batang Beruh Community Health Center. The population of this study consisted of patients diagnosed with pulmonary tuberculosis. The sampling technique used was probability sampling with a random sampling method, resulting in a total sample of 40 respondents. Primary data were collected in this study.The results of this study are expected to encourage respondents to improve their knowledge by actively seeking information and being more concerned about personal and community health in order to prevent the transmission of pulmonary tuberculosis. Additionally, improvements in patient behavior are anticipated through the active involvement and cooperation of medical personnel and other healthcare professionals in providing accurate and appropriate health information